Preventive effects of Spirogyra neglecta and a polysaccharide extract against dextran sodium sulfate induced colitis in mice - Taya S. (2017)
Ulcerative colitis (UC) results from colonic epithelial barrier defects and impaired mucosal immune responses. In this study, we aimed to investigate the modifying effects of a Spirogyra neglecta extract (SNE), a polysaccharide extract (PE) and a chloroform fraction (CF) on dextran sodium sulfate (DSS)-induced colitis in mice and to determine the mechanisms. To induce colitis, ICR mice received 3% DSS in their drinking water for 7 days. Seven days preceding the DSS treatment, oral administration of SNE, PE and CF at doses of 50, 25 and 0.25 mg/kg body weight (low dose), 200, 100 and 1 mg/kg body weight (high dose) and vehicle was started and continued for 14 days. Histologic findings showed that DSS-induced damage of colonic epithelial structure and inflammation was attenuated in mice pre-treated with SNE, PE and CF. Furthermore, SNE and PE significantly protected colonic epithelial cells from DSS-induced cell cycle arrest, while SNE, PE and CF significantly diminished apoptosis. Proteome analysis demonstrated that SNE and PE might ameliorate DSS-induced colitis by inducing antioxidant enzymes, restoring impaired mitochondria function, and regulating inflammatory cytokines, proliferation and apoptosis. These results suggest that SNE and PE could prevent DSS-induced colitis in ICR mice by protection against and/or aiding recovery from damage to the colonic epithelium, reducing ROS and maintaining normal mitochondrial function and apoptosis.